On The Poems of Shah Ismail Khatai (Journal of Alevism-Bektashism Studies, 2024)
The study examines the linguistic and cultural heritage within the Alevi-Bektashi belief system, focusing particularly on oral traditions and hymns (nefes). The analysis aims to explain the theological and historical background of the Alevi-Bektashi belief system in relation to Sufi Islam centers in Western Europe, supported by field data. The fieldwork conducted in Thrace in 1999 reveals how the Alevi-Bektashi belief system has maintained its vitality and adapted to changes over time through oral transmission, particularly via the hymns collected during this research. These hymns emphasize key messages such as hospitality, spiritual devotion, and human limitations in the face of divine power. Additionally, the study explores the similarities between the Turks’ pre-Islamic cultural elements and the Hungarians’ pre-Christian traditions. From a linguistic perspective, the expressions and vocabulary used in these hymns reflect the historical evolution of the Turkish language and its interactions with Hungarian. Specifically, traces of Turkish-origin words and structures in Hungarian provide concrete evidence of these interactions. The research highlights the use of Middle Turkish in Hatayi’s hymns, which embodies the linguistic characteristics of the period and elements of pre-Islamic Turkish culture. The Alevi-Bektashi belief system, as illustrated in Hatayi’s hymns, offers a rich theological and linguistic heritage. This study aims to shed light on the historical, literary, and linguistic dimensions of this belief system, contributing to the preservation and understanding of its cultural legacy.